O controle jurisdicional de convencionalidade: análise do tratado internacional das pessoas com deficiência em relação à legislação previdenciária brasileira e argentina - Huber, Guilherme Ziegler (2016)
This work has the objective analysis about the treatment of the conventionality control laws in the Brazilian and Argentine legal scenario. As we search problem is to analyze what the hierarchy of international human rights treaties entered into both legal systems and, in result, analyze the existence or not of vertical compatibility and material between the laws governing the retirement of people with disabilities in each of these countries on the International Convention on the Rights of Persons with Disabilities. Regarding methodology, we chose to use the deductive method of approach, based on the study of the concepts brought by the International Convention, the Brazilian legislation and the Argentine legislation with the aim of achieving the ability to analyze it in everyday cases from the application of conventionality control theories. Still, regarding the method of procedure, because of the need precisely to point out that the similarities and dissimilarities between the domestic laws of each country in relation to international rule. In this way, it was noticed that lies a discrepancy regarding the person of significance with disabilities in each of these standards, since the international treaty brings an extremely broad definition of disabled person in order to seal the right to a large section of society that because of medical, social, educational, vocational, psychological or cultural barriers are outside the social life and the labor market. In contrast to this, Brazilian law restricts the finding of disability to cases of medical and social order, although the Argentine law restricts only to medical disability cases. Such existing conceptual discrepancy between the rules affect too much a large part of society, since, acting in such a way, one is undeniably excluding the legal protection a large portion of society that fails to include socially and professionally because of issues beyond the mere medical or social look. Therefore, it shows extremely important study with the aim of triggering the incompatibility of existing laws can be act to modify the current state of affairs and, by consequence, to include a greater number of individuals in the legislative seal in strict observance of the auspices of the human rights of persons with disabilities